INSTITUTIONAL MECHANISMS AND TECHNOLOGIES OF PUBLIC REGULATION OF INDUSTRIAL DEVELOPMENT IN THE PROCESSES OF POWER DECENTRALIZATION - Khodiakova, K. (Pressing Problems of Public Administration, 2019)
Today, Ukraine is on the path of many reforms that are driven by modern global challenges, including the reform of decentralization. Despite of the wide range of research, the issue of public regulation of regional industry development at the level of territorial communities remains relevant and open. Issues of decentralization and public administration of regional development, in particular the institutional mechanisms are discussed in the works of A. Gospodini, M. Keating, A. Auzan, V. Zotova, O. Lukashova, O. Fedorchak, N. Filipova. Studies on the use of PPP mechanisms have been conducted by such scientists as T. Blokhin, B. Danylyshyn, A. Nikitin, and T. Samofalova. The paper objective is to improve the institutional mechanisms and technologies of public regulation of industrial development in the processes of power decentralization. The institutional component of public regulation of industrial development under decentralization conditions is considered in the article. Advantages of public regulation of industry development by local self-government bodies over central government bodies are presented. An analysis has been carried out and duplication of functions of the subjects of industry management has been revealed. The justification for improving the institutional environment of industrial development based on the cooperation between the state and business is presented. Sustainable development of the industry of the regions is a complex goal of the state, local governments and private investors. In order to ensure the financial, social, environmental, innovation, investment and other functions of the regions, in the context of decentralization, it is appropriate to use PPP tools.